Innovative Learning Processes in the Teaching of Accounts: Its Influence on Student’s Attitudes - Witarsa Witarsa (International Journal of Educational Review, 2023)
This paper focuses on the students’ attitudes towards the learning of accounts in vocational schools. The author aims to examine how innovative teaching and learning processes influence students’ attitudes towards accounts course. An explanatory survey method has been used to exploit and explain the data. The results of the study show that a teacher’s innovative teaching and learning process influences students’ attitudes towards the learning of accounts course. The learning of accounts is greatly influenced by the students’ attitudes which can be reshaped by the help of an innovative teaching-learning process. This means that innovative teaching is of positive impact in teaching accounts in vocational schools across Indonesia.